Achieving 9.6% efficiency in 304 nm p-AlGaN UVB LED via increasing the holes injection and light reflectance - Khan, M. Ajmal; Maeda, Noritoshi; Yun, Joosun; Jo, Masafumi; Yamada, Yoichi; Hirayama, Hideki (Scientific reports, 2022)
Crystal growth of eco-friendly, ultrawide bandgap aluminium gallium nitride (AlGaN) semiconductor-based ultraviolet-B (UVB) light-emitting diodes (LEDs) hold the potential to replace toxic mercury-based ultraviolet lamps. One of the major drawbacks in the utilisation of AlGaN-based UVB LEDs is their low efficiency of about 6.5%. The study investigates the influence of Al-graded p-type multi-quantum-barrier electron-blocking-layer (Al-grad p-MQB EBL) and Al-graded p-AlGaN hole source layer (HSL) on the generation and injection of 3D holes in the active region. Using the new UVB LED design, a significant improvement in the experimental efficiency and light output power of about 8.2% and 36 mW is noticed. This is accomplished by the transparent nature of Al-graded Mg-doped p-AlGaN HSL for 3D holes generation and p-MQB EBL structure for holes transport toward multi-quantum-wells via intra-band tunnelling. Based on both the numerical and experimental studies, the influence of sub-nanometre scale Ni film deposited underneath the 200 nm-thick Al-film p-electrode on the optical reflectance in UVB LED is investigated. A remarkable improvement in the efficiency of up to 9.6% and light output power of 40 mW, even in the absence of standard package, flip-chip, and resin-like lenses, is achieved on bare-wafer under continuous-wave operation at room temperature. The enhanced performance is attributed to the use of Al-graded p-MQB EBL coupled with softly polarised p-AlGaN HSL and the highly reflective 0.4 nm-thick Ni and 200 nm-thick Al p-electrode in the UVB LED. This research study provides a new avenue to improve the performance of high-power p-AlGaN-based UVB LEDs and other optoelectronic devices in III–V semiconductors.